2015
DOI: 10.1055/s-0035-1547738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of experimental thyrotoxicosis onto blood coagulation – A proteomics study

Abstract: protein abundances and fT 4 levels were calculated using a Pearson correlation. Results: All subjects developed biochemical thyrotoxicosis, and this effect was reversed within the first 4 weeks of follow-up. None of the volunteers noticed any subjective symptoms. Levels of 10 proteins involved in the coagulation cascade specifically correlated with fT 4 , supporting an influence of thyroid hormone levels on blood coagulation even at nonpathological levels. Conclusions: The results suggest that experimental thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In the meta‐analysis, it was concluded that hyperthyroidism shifts the hemostatic balance towards a hypercoagulable and hypofibrinolytic state, which was observed in both endogenous and exogenous hyperthyroidism, and in both subclinical and overt hyperthyroidism. After publication of this systematic review, another study of experimental hyperthyroidism added that the procoagulant factors XIII subunit B, FII, FV and FXI also positively correlated with higher FT 4 levels (regression coefficient ≥ 0.8) . Also, a positive correlation could be found for FIX.…”
Section: Effects Of Thyroid Hormone On Markers Of Coagulation and Fibmentioning
confidence: 95%
“…In the meta‐analysis, it was concluded that hyperthyroidism shifts the hemostatic balance towards a hypercoagulable and hypofibrinolytic state, which was observed in both endogenous and exogenous hyperthyroidism, and in both subclinical and overt hyperthyroidism. After publication of this systematic review, another study of experimental hyperthyroidism added that the procoagulant factors XIII subunit B, FII, FV and FXI also positively correlated with higher FT 4 levels (regression coefficient ≥ 0.8) . Also, a positive correlation could be found for FIX.…”
Section: Effects Of Thyroid Hormone On Markers Of Coagulation and Fibmentioning
confidence: 95%
“…Decreased APTT (Lippi et al, 2009) and predisposition to a hypercoagulable state (Franchini, Lippi, Manzato, Vescovi, & Targher, 2010) are reported in humans with natural hyperthyroidism. In healthy volunteers given 250 μg/day for 8 weeks, the resultant biochemical thyrotoxicosis induced increased expression of numerous procoagulant clotting factors and decreased fibrinolytic factors (Engelmann et al, 2015). There were no changes in PT, APTT, and PIVKA (Proteins Induced by Vitamin K Absence or Antagonists) values in hyperthyroid cats before and after treatment with methimazole (Randolph et al, 2000).…”
Section: Discussionmentioning
confidence: 91%
“…Engelmann et al 11 and Pietzner and coworkers 10 reported changes in the coagulation factors in the plasma proteome in a cohort of 16 healthy men made hyperthyroid by oral T 4 for 8 weeks. The coagulation proteins that showed the most significant increases and correlation with the rise in serum-free T 4 included factors FXIII B subunit, FIX, an inhibitor of activated protein C, SERPIN A5, and α2 antiplasmin (Table 1).…”
Section: Observations and Pathophysiologymentioning
confidence: 99%